Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the system of simultaneous equations:
[tex]\[ \begin{aligned} x & = 7 - 3y \\ x^2 - y^2 & = 39 \end{aligned} \][/tex]
we'll proceed step-by-step:
### Step 1: Substitute [tex]\( x \)[/tex] from the first equation into the second equation
Given:
[tex]\[ x = 7 - 3y \][/tex]
Substitute [tex]\( x = 7 - 3y \)[/tex] into the second equation [tex]\( x^2 - y^2 = 39 \)[/tex]:
[tex]\[ (7 - 3y)^2 - y^2 = 39 \][/tex]
### Step 2: Expand and simplify
Expand [tex]\( (7 - 3y)^2 \)[/tex]:
[tex]\[ (7 - 3y)^2 = 49 - 42y + 9y^2 \][/tex]
Now substitute this back in:
[tex]\[ 49 - 42y + 9y^2 - y^2 = 39 \][/tex]
Simplify the equation:
[tex]\[ 49 - 42y + 8y^2 = 39 \][/tex]
### Step 3: Combine like terms and solve for [tex]\( y \)[/tex]:
[tex]\[ 8y^2 - 42y + 49 - 39 = 0 \][/tex]
[tex]\[ 8y^2 - 42y + 10 = 0 \][/tex]
### Step 4: Solve the quadratic equation
To solve [tex]\( 8y^2 - 42y + 10 = 0 \)[/tex], we can use the quadratic formula:
[tex]\[ y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 8 \)[/tex], [tex]\( b = -42 \)[/tex], and [tex]\( c = 10 \)[/tex].
So,
[tex]\[ y = \frac{42 \pm \sqrt{(-42)^2 - 4 \cdot 8 \cdot 10}}{2 \cdot 8} \][/tex]
[tex]\[ y = \frac{42 \pm \sqrt{1764 - 320}}{16} \][/tex]
[tex]\[ y = \frac{42 \pm \sqrt{1444}}{16} \][/tex]
[tex]\[ y = \frac{42 \pm 38}{16} \][/tex]
This gives us two solutions for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{42 + 38}{16} = \frac{80}{16} = 5 \][/tex]
or
[tex]\[ y = \frac{42 - 38}{16} = \frac{4}{16} = \frac{1}{4} \][/tex]
### Step 5: Substitute [tex]\( y \)[/tex] back to find [tex]\( x \)[/tex]:
1. When [tex]\( y = 5 \)[/tex]:
[tex]\[ x = 7 - 3 \cdot 5 = 7 - 15 = -8 \][/tex]
2. When [tex]\( y = \frac{1}{4} \)[/tex]:
[tex]\[ x = 7 - 3 \cdot \frac{1}{4} = 7 - \frac{3}{4} = \frac{28}{4} - \frac{3}{4} = \frac{25}{4} \][/tex]
### Step 6: List the solutions
The solutions for the system of equations are:
[tex]\[ (x, y) = (-8, 5) \quad \text{and} \quad \left( \frac{25}{4}, \frac{1}{4} \right) \][/tex]
Thus, the correct solutions are:
[tex]\[ (x, y) = (-8, 5) \quad \text{and} \quad \left( \frac{25}{4}, \frac{1}{4} \right) \][/tex]
[tex]\[ \begin{aligned} x & = 7 - 3y \\ x^2 - y^2 & = 39 \end{aligned} \][/tex]
we'll proceed step-by-step:
### Step 1: Substitute [tex]\( x \)[/tex] from the first equation into the second equation
Given:
[tex]\[ x = 7 - 3y \][/tex]
Substitute [tex]\( x = 7 - 3y \)[/tex] into the second equation [tex]\( x^2 - y^2 = 39 \)[/tex]:
[tex]\[ (7 - 3y)^2 - y^2 = 39 \][/tex]
### Step 2: Expand and simplify
Expand [tex]\( (7 - 3y)^2 \)[/tex]:
[tex]\[ (7 - 3y)^2 = 49 - 42y + 9y^2 \][/tex]
Now substitute this back in:
[tex]\[ 49 - 42y + 9y^2 - y^2 = 39 \][/tex]
Simplify the equation:
[tex]\[ 49 - 42y + 8y^2 = 39 \][/tex]
### Step 3: Combine like terms and solve for [tex]\( y \)[/tex]:
[tex]\[ 8y^2 - 42y + 49 - 39 = 0 \][/tex]
[tex]\[ 8y^2 - 42y + 10 = 0 \][/tex]
### Step 4: Solve the quadratic equation
To solve [tex]\( 8y^2 - 42y + 10 = 0 \)[/tex], we can use the quadratic formula:
[tex]\[ y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 8 \)[/tex], [tex]\( b = -42 \)[/tex], and [tex]\( c = 10 \)[/tex].
So,
[tex]\[ y = \frac{42 \pm \sqrt{(-42)^2 - 4 \cdot 8 \cdot 10}}{2 \cdot 8} \][/tex]
[tex]\[ y = \frac{42 \pm \sqrt{1764 - 320}}{16} \][/tex]
[tex]\[ y = \frac{42 \pm \sqrt{1444}}{16} \][/tex]
[tex]\[ y = \frac{42 \pm 38}{16} \][/tex]
This gives us two solutions for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{42 + 38}{16} = \frac{80}{16} = 5 \][/tex]
or
[tex]\[ y = \frac{42 - 38}{16} = \frac{4}{16} = \frac{1}{4} \][/tex]
### Step 5: Substitute [tex]\( y \)[/tex] back to find [tex]\( x \)[/tex]:
1. When [tex]\( y = 5 \)[/tex]:
[tex]\[ x = 7 - 3 \cdot 5 = 7 - 15 = -8 \][/tex]
2. When [tex]\( y = \frac{1}{4} \)[/tex]:
[tex]\[ x = 7 - 3 \cdot \frac{1}{4} = 7 - \frac{3}{4} = \frac{28}{4} - \frac{3}{4} = \frac{25}{4} \][/tex]
### Step 6: List the solutions
The solutions for the system of equations are:
[tex]\[ (x, y) = (-8, 5) \quad \text{and} \quad \left( \frac{25}{4}, \frac{1}{4} \right) \][/tex]
Thus, the correct solutions are:
[tex]\[ (x, y) = (-8, 5) \quad \text{and} \quad \left( \frac{25}{4}, \frac{1}{4} \right) \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.